The influence of thermal annealing on the photoconducting properties of BaSnO3 films - Bridoux, German (2021)
Starting from high-quality oxygen-deficient BaSnO3 films, we have monitored the evolution of their electrical conducting and photoconducting properties after subsequent post-thermal annealing in oxygen. In this way, we have been able to modify the electrical conductivity of the film by at least three orders of magnitude (from 18.2 to 0.013 ω - 1 m-1) by simply reducing the oxygen vacancies concentration after each thermal annealing. Even though the film holds its semiconducting-like behavior, we have observed a modification of the hopping parameters concomitant with a decrease in the Fermi energy level as the electrical conductivity is reduced. Similarly, the effective energy gap extracted from photoconductance spectroscopy measurements decreases as the Fermi energy level decreases suggesting the presence of in-gap states generated by oxygen vacancies. A direct energy bulk gap value of (3.8 ± 0.1) eV was obtained. While the photoconductivity increases from ≃ 4.6 to 73%, its slow time constants become less dominant as the electrical conductivity is decreased in accordance with a reduction of the oxygen vacancies density, which play a key role as electron-traps.